2012
DOI: 10.1107/s0907444912040206
|View full text |Cite
|
Sign up to set email alerts
|

X-ray study of the conformational changes in the molecule of phosphopantetheine adenylyltransferase fromMycobacterium tuberculosisduring the catalyzed reaction

Abstract: Structures of recombinant phosphopantetheine adenylyltransferase (PPAT) from Mycobacterium tuberculosis (PPATMt) in the apo form and in complex with the substrate ATP were determined at 1.62 and 1.70 Å resolution, respectively, using crystals grown in microgravity by the counter-diffusion method. The ATP molecule of the PPATMt-ATP complex was located with full occupancy in the active-site cavity. Comparison of the solved structures with previously determined structures of PPATMt complexed with the reaction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…The first reported protein crystallization experiments in microgravity, performed in 1984, described the growth of lysozyme and b-galactosidase crystals on Spacelab-1 (Littke and John, 1984). Since then in subsequent space shuttle missions, unmanned satellite missions, on the Russian space station and on the International Space Station (ISS), more than 100 different proteins have been crystallized under microgravity conditions (DeLucas et al, 1986;Krauspenhaar et al, 2002;Snell et al, 1997;Timofeev et al, 2012a;Vallazza et al, 2002). In 1989, Asano et al performed a series of crystal growth experiments for bovine pancreatic ribonuclease S under microgravity conditions using the COSIMA 2 system (Asano et al, 1992;Plaas-Link and Cornier, 1988).…”
Section: Fluorescent Labeling Of Protein Aggregatesmentioning
confidence: 99%
“…The first reported protein crystallization experiments in microgravity, performed in 1984, described the growth of lysozyme and b-galactosidase crystals on Spacelab-1 (Littke and John, 1984). Since then in subsequent space shuttle missions, unmanned satellite missions, on the Russian space station and on the International Space Station (ISS), more than 100 different proteins have been crystallized under microgravity conditions (DeLucas et al, 1986;Krauspenhaar et al, 2002;Snell et al, 1997;Timofeev et al, 2012a;Vallazza et al, 2002). In 1989, Asano et al performed a series of crystal growth experiments for bovine pancreatic ribonuclease S under microgravity conditions using the COSIMA 2 system (Asano et al, 1992;Plaas-Link and Cornier, 1988).…”
Section: Fluorescent Labeling Of Protein Aggregatesmentioning
confidence: 99%
“…3537 These studies, together with the availability of crystal structures of a number of CoA pathway enzymes for use in structure-guided drug design, provided further support for investigating the CoA pathway as an attractive source of new TB drug targets, encouraging the development of inhibitors against various pathway enzymes. 9,13,3841 However, despite resource-intensive efforts that led to the identification of potent inhibitors of Mtb PanC and PanK enzymes, these molecules failed to translate into lead compounds with significant whole-cell activity. 13,42,43 Using cKD mutants of Mtb as tools to assess target vulnerability and the target selectivity of small-molecule inhibitors in whole Mtb cells, we 21 and others 43 concluded that these failures might be explained, at least in part, by the relative invulnerability of Mtb to depletion of PanC and PanK.…”
mentioning
confidence: 99%
“…In the MES‐bound form, the sulfate moiety binds in the oxyanion hole in the catalytic pocket. However, its binding is not enough to trigger the full reorientation of the C‐terminal helix as shown in the NTP binding forms ,…”
Section: Resultsmentioning
confidence: 99%